Catalytic Enantioselective Aminopalladation–Heck Cascade. Issue 13 (17th February 2021) - He, Yu‐Ping; Cao, Jian; Wu, Hua; Wang, Qian; Zhu, Jieping
Abstract: Domino processes initiated by intramolecular nucleopalladation of alkynes have been developed into powerful synthetic tools for the synthesis of functionalized heterocycles. However, a catalytic enantioselective version of this class of reactions remains scarce. We report herein that reaction of 2‐alkynylanilines with prochiral cyclopentenes in the presence of a catalytic amount of Pd(OAc)2, a chiral bidentate pyrox ligand and O2 as terminal oxidant affords the structurally diverse indole‐cyclopentene conjugates bearing two stereocenters in a highly diastereo‐ and enantio‐selective manner. One of the products is converted to a heavily functionalized tetracyclic indolinone derivative. Abstract : Reaction of 2‐alkynylanilines with prochiral cyclopentenes in the presence of a catalytic amount of Pd(OAc)2, a chiral bidentate pyrox ligand and O2 as terminal oxidant affords structurally diverse indole‐cyclopentene conjugates bearing two stereocenters in a highly diastereo‐ and enantio‐selective manner.